Prevalence of Hypertension and Related Factors Among Older People In Nursing Home of Jember, East Java, Indonesia - Rismawan Adi Yunanto; Tantut Susanto; Hanny Rasni; Latifa Aini Susumaningrum; Kholid Rosyidi Muhammad Nur (Faculty of Nursing, Universitas Jember, 2019)
Older people (OP) have high risk for hypertension related with changing during older process in particularly system of cardiovascular. The purpose of this study is to identify prevalence of hypertension and related factors among OP in nursing home of Jember, East Java, Indonesia. A cross-sectional study was conducted among 42 of OP in nursing home. A self-administered questionnaire was used to identify characteristic of participants. Data of activity daily living, cognitive function, emotional status, depression status, and spiritual activity was measured using Katz Index of Independence in Activities of Daily Living (ADL), Short Portable Mental Status Questionnaire (SPMSQ), The Mini Mental State Examination (MMSE), Depression Anxiety Stress Scale 14 (DASS-14), and Daily Spiritual Experience Scale (DSES), respectively. Blood pressure was measured using a standard protocol employing a stethoscope and sphygmomanometer. A logistic regression analysis was used to determine factors related to hypertension among OP. Blood pressure of systolic and diastolic among OP were 131.90 ± 16.56 mmHg and 82.02 ± 10.18 mmHg, respectively. The prevalence of systolic and diastolic hypertension among OP in nursing home were 38.1% and 21.4%, respectively. The factors of systolic hypertension were age (p= 0.038), activity daily living (p= 0.043), depression status (p= 0.012), and spiritual activity (p= 0.015). Meanwhile, factors of diastolic hypertension were age (p= 0.041) and education (p= 0.049). Increasing age of OP related a risk factor of hypertension by supported by there are psychological problems like depression, although could be reduced by existence of spiritual activity of OP. Provision of health education on changes in the cardiovascular system and adaptation of lifestyle changes in the OP will be able to reduce hypertension factors in the OP.